Winery By-Products In Vitro and In Vivo Effects on Atherothrombotic Markers: Focus on Platelet-Activating Factor - Maria Choleva; Smaragdi Antonopoulou; Elizabeth Fragopoulou (Frontiers in Bioscience-Landmark)
Platelet aggregation and inflammation play a crucial role in atherothrombosis. Wine contains micro-constituents of proper quality and quantity that exert cardioprotective actions, partly through inhibiting platelet-activating factor (PAF), a potent inflammatory and thrombotic lipid mediator. However, wine cannot be consumed extensively due to the presence of ethanol. Alternatively, winery by-products are abundant in similar-to-wine micro-constituents that could be used in food fortification and dietary supplements. Also, the vinification process produces millions of tons of by-products worldwide, posing an environmental matter of waste management. Therefore, the purpose of this literature review is to update the existing data concerning the in vitro anti-platelet and anti-inflammatory properties of winery by-product extracts and their possible health effects through controlled clinical trials in humans, specifically focused on their effects on PAF’s actions. Data from in vitro studies report that winery by-product compounds are able to inhibit platelet aggregation against several aggregation factors, as well as to downregulate inflammatory markers. Among their actions, extracts or phenolic compounds present in winery by-products inhibit PAF’s actions, a potent inflammatory and thrombotic mediator. Similar conclusions have been drawn from human supplementation studies, which suggest that winery by-product extracts may have beneficial biological effects on the cardiovascular system. Evidence from long-term studies shows that consumption may lower total and low density lipoprotein (LDL) cholesterol, improve insulin sensitivity, decrease lipid and protein oxidative damage, enhance antioxidant capacity, and have mild anti-inflammatory action toward reducing cytokine expression and levels. Data from the limited postprandial studies report that the acute consumption of winery by-product extracts improves glycemic response and reduces platelet reactivity to aggregatory stimuli. Although wine extracts and phenolic compounds have been reported to inhibit PAF’s actions and reduce the activity of its biosynthetic enzymes, no data exist concerning the influence of winery by-product extracts. In the future, additional long-term randomized controlled trials or postprandial studies are needed to draw definitive conclusions and establish a viable cardioprotective strategy that incorporates the sustainable use of winery by-products.